THE ROLE OF THE REGIONAL TECHNICAL IMPLEMENTATION OF WOMEN AND CHILDREN (UPTD PPA) IN HANDLING CASES OF SEXUAL VIOLENCE AGAINST CHILDREN IN THE CITY OF SUKABUMI - Rika Binti Jajul; Yana Fajar FY Basori; Rizki Hegia Sampurna (DIA: Jurnal Administrasi Publik, 2023)
Sexual violence is any activity that consists of sexual activity carried out by adults to children and by children to other children. This research focuses on the role of the Regional Technical Implementation Unit for the Protection of Women and Children (UPTD PPA) and what are the supporting factors as well as obstacles in handling cases of sexual violence against children in Sukabumi City. This research has several problems, including that Sukabumi City does not yet have a safe house for victims of sexual violence and there are still increasing cases of child sexual violence, while Sukabumi City won the title of Child Worthy City (KLA) at the Intermediate level in 2016-2019 and rose to the Nidya level in 2021. The theory used to find out how the role of UPTD PPA in handling cases of child sexual violence is the role dimension of Arimbi et al (2003: 45). The method used in this study is descriptive qualitative, with data collection using observation, interviews, documents, audio and visual materials. The results of this study show that the role of the UPTD PPA in handling the case has been running in accordance with laws and regulations, but it is still not optimal. When viewed from one of the 6 service strategies that have not yet run, namely in temporary shelter. Then the infrastructure is incomplete and there is still a lack of human resources (HR) at the UPTD PPA.